Temporal Changes in Vaginal Microbiota and Genital Tract Cytokines Among South African Women Treated for Bacterial Vaginosis - Mtshali, Andile; San, James Emmanuel; Osman, Farzana; Garrett, Nigel; Balle, Christina; Giandhari, Jennifer; Onywera, Harris; Mngomezulu, Khanyisile; Mzobe, Gugulethu; de Oliveira, Tulio; Rompalo, Anne; Mindel, Adrian; et al. (Frontiers in Immunology, 2021)
The standard treatment for bacterial vaginosis (BV) with oral metronidazole is often ineffective, and recurrence rates are high among African women. BV-associated anaerobes are closely associated with genital inflammation and HIV risk, which underscores the importance of understanding the interplay between vaginal microbiota and genital inflammation in response to treatment. In this cohort study, we therefore investigated the effects of metronidazole treatment on the vaginal microbiota and genital cytokines among symptomatic South African women with BV [defined as Nugent score (NS) ≥4] using 16S rRNA gene sequencing and multiplex bead arrays. Among 56 BV-positive women, we observed short-term BV clearance (NS <4) in a proportion of women six weeks after metronidazole treatment, with more than half of these experiencing recurrence by 12 weeks post-treatment. BV treatment temporarily reduced the relative abundance of BV-associated anaerobes (particularly Gardnerella vaginalis and Atopobium vaginae) and increased lactobacilli species (mainly L. iners), resulting in significantly altered mucosal immune milieu over time. In a linear mixed model, the median concentrations of pro-inflammatory cytokines and chemokines were significantly reduced in women who cleared BV compared to pre-treatment. BV persistence and recurrence were strongly associated with mucosal cytokine profiles that may increase the risk of HIV acquisition. Concentrations of these cytokines were differentially regulated by changes in the relative abundance of BVAB1 and G. vaginalis. We conclude that metronidazole for the treatment of BV induced short-term shifts in the vaginal microbiota and mucosal cytokines, while treatment failures promoted persistent elevation of pro-inflammatory cytokine concentrations in the genital tract. These data suggest the need to improve clinical management of BV to minimize BV related reproductive risk factors.